2009
DOI: 10.1242/dev.031781
|View full text |Cite
|
Sign up to set email alerts
|

Nkx6-1 controls the identity and fate of red nucleus and oculomotor neurons in the mouse midbrain

Abstract: Little is known about the cues controlling the generation of motoneuron populations in the mammalian ventral midbrain. We show that Otx2 provides the crucial anterior-posterior positional information for the generation of red nucleus neurons in the murine midbrain. Moreover, the homeodomain transcription factor Nkx6-1 controls the proper development of the red nucleus and of the oculomotor and trochlear nucleus neurons. Nkx6-1 is expressed in ventral midbrain progenitors and acts as a fate determinant of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 62 publications
2
80
0
8
Order By: Relevance
“…Instead, these progenitors, now included in the Shh::Cre recombinase domain, subsequently generate the Brn3aϩ (␤-galϩ) cohort (10.5 dpc onward). This model is consistent with rodent birthdating studies showing that the neurogenetic interval of the 3N precedes that of the RN (25). Accordingly, the Isl1/2ϩ and Brn3aϩ neurons are in register along the ventricular-pial axis of the 12.5-dpc embryo.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, these progenitors, now included in the Shh::Cre recombinase domain, subsequently generate the Brn3aϩ (␤-galϩ) cohort (10.5 dpc onward). This model is consistent with rodent birthdating studies showing that the neurogenetic interval of the 3N precedes that of the RN (25). Accordingly, the Isl1/2ϩ and Brn3aϩ neurons are in register along the ventricular-pial axis of the 12.5-dpc embryo.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we focused on the homeodomain transcription factor Dbx1, because it has been shown that Dbx1 mRNA is expressed by progenitor cells in the dorsal midbrain during the time when midbrain commissural neurons are generated (Mastick et al, 1997;Prakash et al, 2009). We first examined the overall expression pattern of Dbx1 in the midbrain using whole-mount immunohistochemistry on flat-mounted midbrain preparations at E11.5.…”
Section: Dbx1 Is Expressed By a Subset Of Neural Progenitors In The Dmentioning
confidence: 99%
“…Forced ectopic expression of Otx2 in the hindbrain floor plate (FP) results in DA neuron production in the hindbrain (Ono et al, 2007), whereas loss of Otx1/2 results in expanded hindbrain at the expense of midbrain (Omodei et al, 2008;Puelles et al, 2004;Simeone et al, 2002). Along the dorsoventral (D-V) axis, several studies have demonstrated that the Shh + /Foxa2 + domain is subdivided into at least two main domains defined by Lmx1a/b and Nkx6-1/Sim1/ Neurog1 (Andersson et al, 2006;Blaess et al, 2011;Hayes et al, 2011;Joksimovic et al, 2009;Nakatani et al, 2010;Nouri et al, 2015;Prakash et al, 2009). The Lmx1a/b domain is the origin of most DA neurons, whereas the Nkx6-1/Sim1/Neurog1 domain is the source of Pou4f1 + red nucleus (RN) neurons and other smaller populations.…”
Section: Introductionmentioning
confidence: 99%